Thromboembolic prophylaxis in hernia surgery - Henry Hoffmann (International Journal of Abdominal Wall and Hernia Surgery, 2018)
INTRODUCTION: Thromboembolic prophylaxis (TP) is an effective strategy to reduce the risk of thromboembolic events such as deep vein thrombosis and pulmonary embolism. In the absence of patient- and procedure-related risk factors, the risk of thromboembolic events is considerably low among surgical patients. Since hernia repair is thought to be a low-risk procedure, the role of TP in patients undergoing hernia surgery is a matter of debate. METHODS: A systematic search of the literature was conducted in Medline/PubMed and the Cochrane database. Forty-eight relevant publications were identified. RESULTS: Overall, there is a paucity of studies specifically investigating the impact of TP in patients undergoing hernia surgery. Available studies demonstrate that the risk of thromboembolic events with TP in inguinal hernia repair is approximately 0.1%, comparable to other low-risk procedures. Lower rates of thromboembolic events are seen in outpatient surgery. Laparoscopy and implanted mesh in the groin do not increase the risk of thromboembolic events. CONCLUSION: Due to the limited data, no recommendation for or against TP in hernia surgery can be made. Further studies are urgently needed to investigate the effect of TP on the risk of thromboembolic events in patients undergoing hernia repair.